Understanding God as a Medium: A Dialogue between Albert Camus and Marshall McLuhan - Simões Pires, Arthur F. (New Explorations, 2023)
This paper discusses the idea that the deity or the divine figure serves as a medium or technology. It does so by establishing a dialogue between Albert Camus and Marshall McLuhan. There are two conceptual pillars to sustain the theoretical framework undertaken in this work: the Camusian notion of philosophical suicide and McLuhan’s aphorism “the medium is the message.” Once it is understood that the idea of God is an abundant aggregator of elements that represents all values of the creed, it is also possible to understand that it defines a relationship between oppressors and those that are oppressed. Since this figure came to be used as a support for religions to act, it has worked as a coercive device as well as it has carried all symbolic aspects of its tenet and have mediated the aforementioned relation between dominators and the dominate.